Comparing the Effects of Selenium-Enriched Yeast and Sodium Selenite Supplementation on Postpartum Depression and Sexual Satisfaction: A Triple-Blind Controlled Clinical Trial - Parnian Rahimi; Azizeh Farshbaf-Khalili; Mahnaz Shahnazi; Alireza Ostarahimi; Marzieh Mohammadi (Journal of Caring Sciences)
Introduction: Postpartum depression (PPD) is the most prevalent postpartum complication, significantly diminishing sexual function in marital life. It may result in visible developmental delays, social and interactive challenges in infants, and marital stress leading to divorce. The present study aimed to examine the effect of organic selenium (Saccharomyces cerevisiae yeast enriched with sodium selenite) and sodium selenite on PPD and sexual satisfaction. Methods: A triple-blind controlled clinical trial was conducted on 108 women after childbirth. Participants were randomly assigned into two intervention groups and one placebo group in a 1:1:1 ratio. Participants were given single, identical 250 mg oral capsule containing 200 µg of organically derived selenium or 200 µg of sodium selenite or placebo daily for 8 weeks. They completed Beck’s depression inventory and the sexual satisfaction questionnaire before and after the intervention white one-way analysis of variance (ANOVA) and analysis of covariance (ANCOVA) tests. The mean score of PPD and sexual satisfaction were assessed. Results: All three groups exhibited identical personal and social profiles. PPD scores were significantly reduced in the intervention groups of organically derived selenium (adjusted mean difference [AMD]=-2.77; 95% CI: -0.97 to -4.57; P=0.003) and organic selenium (AMD=-1.77; 95% CI: -0.00 to -3.53; P=0.04) compared to control group by adjusting the baseline values. No significant difference was observed in the sexual satisfaction of intervention groups compared to the placebo at the end of intervention (P=0.19). Conclusion: Both organically derived and inorganic selenium could improve PPD. However, the decline rate was greater in the group receiving yeast-derived selenium. No statistically significant changes were observed in sexual satisfaction following supplementation.